The ICC at 25: Lessons Learnt (Studies of the Central European Professors’ Network, 2025)
This book marks the 25th anniversary of the adoption of the Rome Statute and provides the readers with the contemporary challenges of the functioning of the International Criminal Court. The concept of the book applies a deductive approach starting from general issues to specific ones. After giving an overview on historical antecedents, establishment, jurisdiction etc., the forthcoming chapters discuss the details of core crimes with thorough case law illustrations. Additionally, the book also touches upon the very own problems of the Court, such as its relationship with Africa, the one with peacekeeping activities, aspects related to non-state actors, the status of victims before the Court, the evolution of environmental and economic crimes etc. The differentia specifica of the book is its “Central European perspective”: On the one hand, it primarily comprises the research results of renown academics and legal professionals of this region, on the other hand, it contains a comprehensive analysis on Central European aspects that are highly relevant from the perspective of international criminal law.